2011
DOI: 10.3747/co.v18i1.695
|View full text |Cite
|
Sign up to set email alerts
|

First- and Second-Line Therapy for Metastatic Urothelial Carcinoma of the Bladder

Abstract: but little improvement has been achieved in the outcomes of patients with advanced or metastatic disease. Almost 90% of those patients eventually succumb to their cancer.For patients who relapse after first-line chemotherapy, the prognosis is generally poor. To date, there is no real consensus on how to best treat these patients, and most of the available evidence stems from small phase ii trials that have mostly failed to show survival benefit over supportive care. The present review provides an update on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 102 publications
1
57
1
5
Order By: Relevance
“…Although bladder cancer is a relatively chemosensitive tumor, showing a response rate of 50-70% to frontline treatments, patients who recur after first-line chemotherapy have a very poor prognosis [5]. Interestingly, a tumor response to prior chemotherapy seems to not affect the outcome of patients treated with second-line chemotherapy, with a PFS that does not overcome 3 months for both patients with or without response to chemotherapy [6].…”
Section: Introductionmentioning
confidence: 98%
“…Although bladder cancer is a relatively chemosensitive tumor, showing a response rate of 50-70% to frontline treatments, patients who recur after first-line chemotherapy have a very poor prognosis [5]. Interestingly, a tumor response to prior chemotherapy seems to not affect the outcome of patients treated with second-line chemotherapy, with a PFS that does not overcome 3 months for both patients with or without response to chemotherapy [6].…”
Section: Introductionmentioning
confidence: 98%
“…7 Other non-platinumbased regimens, such as gemcitabine in combination with a taxane, have been evaluated in phase 2 studies in this setting and shown to have efficacy, although response rates and overall survival are lower than in those receiving platinumbased chemotherapy. 8 As well as those not fit enough for a platinum-based regimen, some patients may have significant comorbidities or poor performance status (3 or 4), in which case best supportive care rather than active systemic therapy is recommended. Early palliative care input is crucial.…”
Section: Wwwtrendsinmenshealthcom Trends In Urology and Men's Health mentioning
confidence: 99%
“…Combination chemotherapy generally improves response rates (0-61%) without improving overall survival (4-14 months). 8 Current UK guidelines support the off-licence use of gemcitabine in combination with either paclitaxel or carboplatin. 11 These data underline the urgent need for effective new treatments, and there is growing evidence that immunotherapy agents are active in this setting.…”
Section: Second-line Chemotherapymentioning
confidence: 99%
“…The lack of approved second-line treatment for TCCU may contribute to approval of VFL for the indication [6]. This is especially true from the perspective of clinical practice that best supportive care should be reserved for unfit patients and earlier provision of new treatments with similar survival benefit as salvage therapy might improve or delay disease-related symptoms [7].…”
Section: Introduction and Current Evidencementioning
confidence: 99%